(untitled) (Linguamática, 2025)
Dependency Grammars (DGs) have gained prominence in recent decades, especially due to their widespread application in Natural Language Processing (NLP). Several syntactic analysis tasks adopt DGs as a formal model, given their efficiency in binary structure representation and syntactic disambiguation (Nivre, 2005; Kübler et al., 2009). Projects such as Universal Dependencies (De Marneffe et al., 2021) have consolidated DGs as the dominant paradigm in multilingual annotation systems, and recent works such as (Lopes et al., 2024; Souza et al., 2024; Duran & Pardo, 2024) demonstrate their ongoing relevance in current research. In this context, the present article aims to introduce the core formal foundations of DGs — connectivity, directionality, hierarchy, and syntactic labelling — by discussing structural definitions of dependency, theoretical principles shared across different models, and finally, demonstrating their application through a simplified version of the Hays and Gaifman Grammar (Hays, 1964; Gaifman, 1965). The scope of this work is limited to the theoretical and abstract characterization of the essential properties of DGs, intending to provide an introductory yet sys- tematic foundation for researchers interested in this approach.